Relaxation of residual stress part 2: relaxation of stage 2 - Zaroog, Omar Suliman; Ali, Aidy; Sahari, Barkawi; Zahari, Rizal (Science Publications, 2009)
Problem statement: Compressive residual stress induced by surface treatment such as shot peening increased component's fatigue life. However the initial induced residual stresses relax during component operating life and it is important to consider the relaxation in the design. Approach: In this study, a 2024-T351 aluminum alloy specimens were shot peened into three shot peening intensities condition to induce compressive residual stresses. Then fatigue test for two loads was performed for the 10, 1000 and 10000 cyclic loads. The initial residual stresses at the initial condition and after 10, 1000 and 10000 cycle of fatigue loading were measured using X-ray diffraction method. Results: The results showed that the relaxation of the residual stress for the load 15.5 kN is less than the relaxation of the load 30 kN for the three shot peening intensity. The maximum relaxation for load 15.5 kN is 46% of the initial residual stress at 10000 cycles for intensity 0.009 A while the maximum relaxation for load 30 kN is 54% at 10000 cycles for the intensity of 0.0054% A. this result indicated that the residual stress relaxation depended on the load amplitude. Conclusion: The initial residual stress did not remain stable during the component's fatigue life. Within the second phase relaxation, micro-plastic strains accumulating from cycle to cycle. The residual stress relaxation for second phase is in logarithmic relationship.